Interactive visualization of large molecular systems with VTX: example with a minimal whole-cell model - Maria, Maxime; Guillaume, Valentin; Guionnière, Simon; Dacquay, Nicolas; Plateau–Holleville, Cyprien; Larroque, Vincent; Lardé, Jean; Naimi, Yassine; Piquemal, Jean-Philip; Levieux, Guillaume; Lagarde, Nathalie; Mérillou, Stéphane; et al. (Frontiers in Bioinformatics, 2025)
VTX is an open-source molecular visualization software designed to overcome the scaling limitations of existing real-time molecular visualization software when handling massive molecular datasets. VTX employs a meshless molecular graphics engine utilizing impostor-based techniques and adaptive level-of-detail (LOD) rendering. This approach significantly reduces memory usage and enables real-time visualization and manipulation of large molecular systems. Performance benchmarks against VMD, PyMOL, and ChimeraX using a 114-million-bead Martini minimal whole-cell model demonstrate VTX’s efficiency, maintaining consistent frame rates even under interactive manipulation on standard computer hardware. VTX incorporates features such as Screen-Space Ambient Occlusion (SSAO) for enhanced depth perception and free-fly navigation for intuitive exploration of large molecular systems. VTX is open-source and free for non commercial use. Binaries for Windows and Ubuntu Linux are available at http://vtx.drugdesign.fr. VTX source code is available at https://github.com/VTX-Molecular-Visualization.